Suplementação de bezerros desmamados em pastagem de Tifton 85 - Pizzuti, Luiz Angelo Damian (2014)
This study aimed to evaluate the effects of concentrated supplementation on weaned calves in Tifton 85 bermudagrass pasture regarding the forage production and the development and animal behavior. Forty-four Braford castrated calves, with initial average age of 4.5 months and initial average body weight (BW) of 128.3+26.7 kg were used. The experimental period lasted 140 days, divided into five periods of 28 days, and the treatments consisted in four levels of supplementation: 0,29; 0,5; 1.0 and 1.5% of BW based on dry matter (DM). The grazing method used was the continuous stocking system with a variable number of regulator calves. The bromatological quality of the pasture suffered variation along the periods. The forage and the leaves blades mass did not differ among the treatments, presenting an average of 6316.16 and 934.88 kg DM ha-1 as well as the canopy height and the forage density 25.47cm and 252.20 kg cm-1respectively. The increase in the level of supplementation decreased linearly the offer of forage and the offer of leaves blades. Independently of the analyzed period it was observed a greater participation of leaves in the layer of 10-20cm. The participation of total leaves did not suffered influence of the supplementation levels, however, it increased linearly in the layer of 20-30cm. The final weights of the treatments 1.0 and 1.5% of BW, 248.27 and 254.27 kg were superior to the treatments 0.29 and 0.5% of BW, 203.86 and 210.82 kg respectively. It was observed a high capacity of support of Tifton 85 with variation from 2336.48 to 3127.97 kg BW ha-1 when it was used 0.29% of BW, until values varying from 2747.51 to 7365.75 kg BW ha-1, when it was used 1.5% of BW. The chest perimeter, hip height, longissimus dorsi area and subcutaneous fat thickness suffered influence, responding linearly and positively to the increase of the level of supplementation. The average grazing time of the calves corresponded to 9h53min; 9h03min; 7h20min and 5h48min and the average time for other activities corresponded to 7h39min; 7h53min; 8h42min and 11h02min, respectively for the treatments 0.29; 0.5; 1.0 and 1.5% of BW. The number of bites per station presented an interaction between treatment and period as well as the bites rate. The Tifton 85 associated with supplementation presents a high capacity of stoking rate with high weight gain per hectare. Higher levels of supplementation allow a better structural development of the calves, being this followed by a higher daily average weight gain, longissimus dorsi area and subcutaneous fat thickness, with greater expressiveness when the supplementation level is increased from 0.5 to 1.0% of BW. The reduction in rumination and grazing time promotes the increase in the time of other activities, however, the decrease in grazing time does not determine a lower rumination time. The processes of displacement of the animals and apprehension of forage are changed by the supplementation and by the variation of the pasture cycle of Tifton 85.